2021
DOI: 10.3389/fneur.2021.732034
|View full text |Cite
|
Sign up to set email alerts
|

Brain Circuits Involved in the Development of Chronic Musculoskeletal Pain: Evidence From Non-invasive Brain Stimulation

Abstract: It has been well-documented that the brain changes in states of chronic pain. Less is known about changes in the brain that predict the transition from acute to chronic pain. Evidence from neuroimaging studies suggests a shift from brain regions involved in nociceptive processing to corticostriatal brain regions that are instrumental in the processing of reward and emotional learning in the transition to the chronic state. In addition, dysfunction in descending pain modulatory circuits encompassing the periaqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 160 publications
0
11
0
Order By: Relevance
“…Usually, low frequency (< 1Hz) stimulation has an inhibitory effect on the brain, while high frequency (> 5Hz) stimulation excite neurons ( 11 ). It has been reported that rTMS relieves various types of pain, such as neuropathic pain after spinal cord injury, stroke or postoperative of trigeminal nerve ( 12 ), migraine ( 13 ), fibromyalgia ( 14 ) and chronic musculoskeletal pain ( 15 ). Even less clinical study has been done on the application of rTMS in patients with cancer pain.…”
Section: Introductionmentioning
confidence: 99%
“…Usually, low frequency (< 1Hz) stimulation has an inhibitory effect on the brain, while high frequency (> 5Hz) stimulation excite neurons ( 11 ). It has been reported that rTMS relieves various types of pain, such as neuropathic pain after spinal cord injury, stroke or postoperative of trigeminal nerve ( 12 ), migraine ( 13 ), fibromyalgia ( 14 ) and chronic musculoskeletal pain ( 15 ). Even less clinical study has been done on the application of rTMS in patients with cancer pain.…”
Section: Introductionmentioning
confidence: 99%
“…Glutamate and GABA are critical to maintaining and regulating many physiological functions and are reported to underlie altered excitability in varying chronic pain conditions [ 62 , 63 ]. The potential for tDCS over DLPFC to modulate ICF and SICI in chronic pain may be due to interconnections between the DLPFC and the periaqueductal gray area and motor cortex [ 64 , 65 , 66 ]. These areas play a key role in descending mechanisms that modulate spinal nociceptive activity [ 64 , 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…The potential for tDCS over DLPFC to modulate ICF and SICI in chronic pain may be due to interconnections between the DLPFC and the periaqueductal gray area and motor cortex [ 64 , 65 , 66 ]. These areas play a key role in descending mechanisms that modulate spinal nociceptive activity [ 64 , 65 , 66 ]. A recent meta-analysis reported that while the balance of glutamate and GABA differed between chronic pain conditions, glutamate and GABA play a key role in the pathophysiology of pain processing and modulation [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…The brain regions involved in pain processing include the primary and secondary somatosensory cortices; primary motor and supplementary motor cortices; insular cortex; anterior cingulate cortex; thalamus; regions within the prefrontal and parietal cortices; and regions involved in emotion, memory, and fear processing in the amygdala, hippocampus, and subcortical structures, including the basal ganglia (Martucci and Mackey, 2018;Geuter et al, 2020). Among these brain regions, cortical sites near the scalp have been investigated as potential targets to reduce pain by non-invasive brain stimulation (NIBS), which can alter cortical excitability through approaches, such as repetitive transcranial magnetic stimulation and transcranial direct current stimulation (O'Connell et al, 2018;Kandiae et al, 2021). Neurophysiological studies using electroencephalography (EEG) and magnetoencephalography (MEG) have demonstrated that neural oscillatory frequencies corresponding to the theta (4-7 Hz), alpha (8-12 Hz), beta (13-29 Hz), and gamma bands (30-100 Hz) are associated with pain processing (Ploner et al, 2017).…”
Section: Introductionmentioning
confidence: 99%